STUDI TENTANG MINAT BELI ULANG KONSUMEN KOPI KAPAL API (PADA KONSUMEN KAPAL API DI BONDOWOSO) - Yudha Praja (UNEJ e-Proceeding)
The purpose of this study was to determine the effect of promotion, brand image and product quality to the buying interest kapal api coffee in Bondowoso. This research is a quantitative research survey. With a sample of 100 respondents. Research results show that partial Promotion significantly influence the buying interest, brand image significantly influence the buying interest, quality of products significantly influence the buying interest. Simultaneously promotion, brand image and product quality and significant positive effect on the buying interest. While the influence of independent variables on the dependent variable in this study was 76.5%.